2010
DOI: 10.4236/jssm.2010.34052
|View full text |Cite
|
Sign up to set email alerts
|

On the Contribution of Student Experience Survey Regarding Quality Management in Higher Education: An Institutional Study in Saudi Arabia

Abstract: We appraise comparatively and analytical data under Student Experience Survey (SES) to discuss the possible generalizability of related College level differentials in Saudi Arabia. For this, data collected from students of two academic programs namely Bachelor of Dental Surgery, College of Dentistry; and B.Sc. Nursing, College of Nursing, University of Dammam, Dammam, Saudi Arabia, were considered. These data relate to experience of students halfway of respective academic program. The percentage of participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Rubaish (2012) indicated that once the global item scores demonstrated a high Educational Studies 437 level of satisfaction, then one can explore the individual items for important clues to plan further improvements. This study demonstrates that the global item scores and the individual item scores are highly correlated (14 out of 20 items falls between 2 and 3 sigma level), and such findings are supported by the findings of earlier studies (Arun Vijay 2013; Nair and Bennet 2011;Rubaish 2010). Thus, by observing the global item results, the educational policy planners can get a policy oriented clue about the quality of experience gained by the students in their academic programmes.…”
Section: Discussion On the Findingssupporting
confidence: 83%
See 3 more Smart Citations
“…Rubaish (2012) indicated that once the global item scores demonstrated a high Educational Studies 437 level of satisfaction, then one can explore the individual items for important clues to plan further improvements. This study demonstrates that the global item scores and the individual item scores are highly correlated (14 out of 20 items falls between 2 and 3 sigma level), and such findings are supported by the findings of earlier studies (Arun Vijay 2013; Nair and Bennet 2011;Rubaish 2010). Thus, by observing the global item results, the educational policy planners can get a policy oriented clue about the quality of experience gained by the students in their academic programmes.…”
Section: Discussion On the Findingssupporting
confidence: 83%
“…6th semester students of College of Medicine and 5th semester students of the College of Nursing). The selection of these students is justified by the previous studies which indicate that for conducting SES, the students who are half way through their academic journey need to be surveyed (Aultman 2006;Rubaish 2010). The Arabic version of the SES tool developed by the NCAAA was translated in to English and utilised in this study to capture students' perceptions.…”
Section: Discussion On the Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each dimension of the survey was graded according to performance criteria reported by Al Rubaish and Al Rubaish on the basis of the level of agreement of the medical interns to the survey items. 14,15 Accordingly, each dimension was graded as either high-quality (mean scores of ≤3.6), acceptable (mean scores of 2.6-3.6) or improvement required (mean scores of >2.6). Subsequently, a multiple regression analysis was conducted to assess the influence of the 10 internship dimensions (independent variables) on overall satisfaction (dependent variable).…”
Section: Methodsmentioning
confidence: 99%